Detection and association of Piscirickettsia salmonis in organ and faeces of coho salmon (Oncorhynchus kisutch) farmed in the sea - Montalico Pongo, Ederson Juan (2021)
The aim of this study was to diagnose the presence of Piscirickettsia salmonis in samples of coho salmon (Oncorhynchus kisutch) from fish farms in the Los Lagos Region, Chile, which presented outbreaks of piscirickettsiosis. In total, 19 fish with clinical signs of piscirickettsiosis were used. Smears of kidney, liver and splenic tissue and intestinal content were made, and processed using the indirect immunofluorescence test (IFAT) for the detection of P. salmonis through a commercial kit. The data obtained were subjected to the Cochran and McNemar Q test in the Chi square distribution. Higher positivity was found in the liver (68.4%) and kidney (52.6%). In addition, the bacterium was found in the faeces (47.4%), indicating that the elimination via the faeces of the agent is possible under farming conditions. By associating the kidney and liver results, only 78.9% of the fish positive for the bacteria could be detected, while by associating the liver, spleen and faeces results, 100% of the fish positive to P. salmonis can be detected.